Inside Chega's membership - Carvalho, J.; Santana Pereira, J.; Marchi, R. (Chega: The new Portuguese far right, 2025)
This chapter examines the characteristics of Chega’s party members in the early 2020s through the analysis of a large N survey to help overcome the lack of overall knowledge on far-right activists. The internal composition of the PRRP shapes their internal development, as well as their electoral success at the polls. Drawing on past literature, this chapter will trace the distribution of Chega’s membership according to three main groups: the extremists, the opportunists, and the moderates. Secondly, this investigation seeks to explore the causal factors that influence the internal composition of Chega’s membership. The conclusions will suggest that Chega’s membership is mainly formed by moderates, followed by opportunists, whilst overt ideological extremism is confined to the fringes of the party’s membership. Male and younger party members are more likely to display an extremist profile than female and older members. Chega’s internal composition reflects its roots in deeply conservative circles and the lack of imposition of a cordon sanitaire by the mainstream parties, particularly the PSD